2007
DOI: 10.1055/s-2007-966844
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary pneumoperitoneum facilitates transgastric access into the peritoneal cavity for natural orifice transluminal endoscopic surgery: A pilot study in a live porcine model

Abstract: Creation of a preliminary pneumoperitoneum with a Veress needle facilitates gastric wall puncture and entrance into the peritoneal cavity without injury to adjacent organs, and can improve the safety of NOTES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 15 publications
0
13
0
1
Order By: Relevance
“…They also suggested that a gastrotomy created by a sphincterotome is larger than that by balloon dilatation which may result in difficulty closing the gastrotomy. Ko et al [11] reported that the preliminary pneumoperitoneum with CO 2 insufflation after puncturing the abdominal wall with a Veress needle could improve the safety of gastrotomy creation. However, this technique, as well as Kantesvoy's PEG-like technique, requires puncturing the abdominal wall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also suggested that a gastrotomy created by a sphincterotome is larger than that by balloon dilatation which may result in difficulty closing the gastrotomy. Ko et al [11] reported that the preliminary pneumoperitoneum with CO 2 insufflation after puncturing the abdominal wall with a Veress needle could improve the safety of gastrotomy creation. However, this technique, as well as Kantesvoy's PEG-like technique, requires puncturing the abdominal wall.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have described various transgastric access techniques such as incision with a needle knife, balloon dilatation after needle knife puncture, incision using sphincterotome after puncture, creation of a submucosal tunnel within the gastric wall, and a PEG-like approach [1,[9][10][11][12]. Balloon dilatation after needle knife puncture is widely used due to the simplicity, ease, and swiftness of the approach.…”
Section: Introductionmentioning
confidence: 99%
“…von Delius et al [12] further evaluated the effect of similar access techniques on the strength of closure. Modifications for access have been demonstrated using preliminary pneumoperitoneum [13] or an overtube [14]. Kim et al [15] compared access through the anterior stomach wall and through the rectosigmoid colon to investigate which access site provided the best approach to the abdominal organs.…”
mentioning
confidence: 99%
“…Furthermore, the issue of uncontrolled high intraabdominal pressures that could lead to adverse hemodynamic effects should be avoided in NOTES procedures. This could be accomplished by connecting a gas pressure monitoring system directly to the endoscope [20] or to a Veress needle that would deliver the insufflation gas transdermally [21]. Taking into account the property of room air in supporting combustion, safe use of this insufflating gas should be limited in laparoscopy or laparoscopic procedures that do not require electrocautery.…”
Section: Discussionmentioning
confidence: 99%